2013
DOI: 10.1080/15374416.2013.850700
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-Based Psychosocial Treatments for Children and Adolescents with Attention-Deficit/Hyperactivity Disorder

Abstract: Objective The purpose of this research was to update the Pelham and Fabiano (2008) review of evidence-based practices for children and adolescents with Attention-Deficit/ Hyperactivity Disorder. Method We completed a systematic review of the literature published between 2008 and 2013 to establish levels of evidence for psychosocial treatments for these youth. The review included the identification of relevant articles using criteria established by the Society of Clinical Child and Adolescent Psychology (see … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
372
0
11

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 521 publications
(414 citation statements)
references
References 60 publications
14
372
0
11
Order By: Relevance
“…It remains unclear which paradigm is the most effective as well as the overall efficacy of inhibition training. Although the evidence-based practices of behavioral management and organizational training interventions are considered well-established practices for children with ADHD, not enough randomized controlled trials of cognitive training have been conducted to determine their efficacy [22]. Accordingly, the present study aimed to compare the effectiveness of various techniques and evaluate whether the training could reduce impulsive behavior and improve social skills in children with ADHD.…”
Section: Journal Of Child and Adolescent Behaviormentioning
confidence: 99%
“…It remains unclear which paradigm is the most effective as well as the overall efficacy of inhibition training. Although the evidence-based practices of behavioral management and organizational training interventions are considered well-established practices for children with ADHD, not enough randomized controlled trials of cognitive training have been conducted to determine their efficacy [22]. Accordingly, the present study aimed to compare the effectiveness of various techniques and evaluate whether the training could reduce impulsive behavior and improve social skills in children with ADHD.…”
Section: Journal Of Child and Adolescent Behaviormentioning
confidence: 99%
“…A review evaluating psychological interventions has demonstrated sufficient evidence to consider behaviour management to be an established and effective intervention for ADHD, either when administered by the parent following training or when used in the classroom [36].…”
Section: Addressing the Imbalance In The Level Of Reward Experiencedmentioning
confidence: 99%
“…Therefore, it is frequently observed that a child will work better for a teacher who cares and takes more interest in him, but works less well following a change of teacher. The long-term aim of behaviour management is that the behavioural change should become generalised as the child matures [36].…”
Section: Addressing the Imbalance In The Level Of Reward Experiencedmentioning
confidence: 99%
“…The important problem is low agreement between different informants (various teachers and parents) in the assessment of the intensity of hyperactivity-impulsivity and inattention symptoms (Amador-Campos, Forns-Santacana, Guardia-Olmos, & Pero-Cebollero, 2006;Stevenson et al, 2005;Schultz & Evans, 2012;Thapar, Langley, O'Donovan, & Owen, 2006). Although guidelines how to integrate parent and teacher DSM symptom ratings of ADHD (i.e., And/Or Rule) exist (Evans, Owens & Bunford, 2014), a dimensional approach makes it easier to use data from multiple sources of information, such as parents, teachers, and the children themselves and assess their intensity on the rating scales (Hudziak et al, 2007). Based on this approach, we can perceive symptoms observed by parents and teachers as related, but distinct dimensions.…”
mentioning
confidence: 99%